Adverse maternal environment leads to cardiac fibrosis in adult male mice. Issue 20 (21st December 2018) - Spearman, Andrew D.; Ke, Xingrao; Fu, Qi; Lane, Robert H.; Majnik, Amber
Abstract : Background: Cardiac fibrosis is a cardinal feature of multiple types of cardiovascular disease, which lead to heart failure. Multiple studies connect adverse maternal environment (AME) with cardiac fibrosis. AME does not always result in fibrosis, though. An additional "insult", such as an adult Western diet (WD), is frequently necessary. The additive effects of AME and adult WD on cardiac fibrosis is not well‐understood. AME can also alter DNA methylation. DNA methyltransferase (DNMT) and ten‐eleven translocation (TET) are methylation modifying genes that regulate DNA methylation, but it is unknown if AME changes cardiac gene expression of DNMT and TET. We sought to use a model of AME and adult WD to investigate the development of cardiac fibrosis and cardiac mRNA expression of DNMT and TET genes. Methods: We exposed dams to WD or control diet (CD) 5 weeks before pregnancy and through lactation. We added environmental stressors during the last third of pregnancy to dams on WD to create AME. Dams on CD experienced no added stressors to create control maternal environment (CME). Male offspring were weaned at Postnatal Week 3 (W3) and placed on WD or CD to create four groups: CME‐CD, CME‐WD, AME‐CD, and AME‐WD. Results: AME‐WD increased cardiac fibrosis in adulthood ( p < .05), whereas AME‐CD and CME‐WD did not. TET1‐3 and DNMT3a mRNA levels decreased in AME versus CME offspring ( p < .01). Conclusion: AME increases susceptibility to cardiac fibrosis in adult male mice. Early‐life changes to TET expression may mediate susceptibility to fibrosis, but further testing is needed.